AB0330 RELATIONSHIP BETWEEN FOREFOOT SYNOVITIS IN RHEUMATOID ARTHRITIS AND WORSENING FOREFOOT DEFORMITY. (June 2019) - Kashiwagura, Takeshi; Kobayashi, Moto; Urayama, Masakazu; Konishi, Natsuo; Itoh, Hiroki; Tani, Takayuki; Aizawa, Toshiaki; Abe, Hidekazu; Suzuki, Norio; Kamo, Keiji; Aonuma, Hiroshi; Sugimura, Yusuke; et al.
Abstract : Background: While the number of rheumatoid arthritis (RA) surgeries has been declining due to advances in pharmacotherapies for RA, forefoot surgeries are on the rise. In recent years, the common use of joint ultrasonography in RA consultations has led to the early detection of synovitis. However, little is known about how much forefoot deformities such as hallux valgus and metatarsophalangeal (MTP) joint dislocation are affected by synovitis in the forefoot of RA patients. Objectives: The present study examined factors involved in forefoot deformity among patients with foot synovitis identified on joint ultrasound. Methods: Subjects (71 patients, 91 feet) were RA patients who had undergone foot joint ultrasonography more than 2 years earlier and underwent standing X-rays of the feet before and after ultrasonography. Surgery cases were excluded. Mean age was 64.9 years (range, 15-90 years). Disease stage was Stage 1 in 14 patients, Stage 2 in 14 patients, Stage 3 in 16 patients, and Stage 4 in 27 patients. According to the Steinbrocker functional classification, RA was Class 1 in 45 patients, Class 2 in 19 patients, Class 3 in 6 patients and Class 4 in 1 patient. Twenty-five patients had been administered biological drugs. At the time of joint ultrasonography, patients were questioned regarding whether they had any complaints involving the forefoot, midfoot or hindfoot (noted separately). The following scans were performed: forefoot (MTP joints 1-5); midfoot (calcaneocuboid, calcaneocuboid and cuneonavicular joints) and hindfoot (peroneal muscle tendon, talocrural joint, talocalcaneal joint and posterior tibial muscle tendon). Foot deformity score (FDS) (hallux valgus angle + first-second intermetatarsal angle [M1 M2 angle] + first-fifth intermetatarsal angle [M1 M5 angle]) was used as the benchmark for forefoot deformity, and an increase >5° was considered to indicate worsening deformity. Results: Forefoot deformity had progressed in 25 patients. Mid- and hindfoot synovitis and the presence of complaints were not associated with deformity. However, significant worsening of FDS was observed in patients with forefoot synovitis or forefoot complaints. While no difference in age, disease activity, biologic disease-modifying antirheumatic drug usage or health assessment questionnaire results were seen in the advanced deformity group, duration of disease was significantly shorter in this group. Conclusion: Mid- and hindfoot synovitis was unrelated to forefoot deformity. MTP joint synovitis in the forefoot was related to forefoot deformity. Continuous synovitis in the forefoot must damage the articular capsule and ligament structure, leading to progression of deformity. As shown by the short duration of the disease in the advanced deformity group, deformity may progress in the early stages among patients with forefoot deformity. Disclosure of Interests: None declared